Solid electrolyte material, solid electrolyte, method for producing solid electrolyte, and all-solid battery

By using amorphous solid electrolyte materials, including lithium, tantalum, phosphorus and oxygen, and boron, niobium, silicon and bismuth, the problem of low ion conductivity of oxide-based solid electrolytes when firing at low temperatures is solved, and the effect of high ion conductivity of sintered at low temperatures is achieved, and production costs and equipment requirements are reduced.

CN115699211BActive Publication Date: 2025-04-15RESONAC CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180041221.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-06-10
Filing Date
2021-06-09
Publication Date
2025-04-15
Estimated Expiration
2041-06-09

AI Technical Summary

Technical Problem

The grain boundary resistance of the oxide-based solid electrolyte is large, which makes it difficult to obtain a sintered body with high ion conductivity when firing at low temperatures. The prior art requires firing at high temperatures, which increases economic and equipment challenges.

Method used

A high-density solid electrolyte material containing lithium, tantalum, phosphorus and oxygen and containing a selected from boron, niobium, silicon and bismuth is obtained by sintering between 500 and 900°C.

Benefits of technology

Even if the firing is performed at a low temperature below 900°C, sufficient lithium ion conductivity can be obtained, which reduces the risk of decomposition and deterioration of the material, and improves economicality and equipment efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003987553940000311
    Figure BDA0003987553940000311
  • Figure BDA0003987553940000331
    Figure BDA0003987553940000331
  • Figure BDA0003987553940000341
    Figure BDA0003987553940000341
Patent Text Reader

Abstract

A technical solution of the present invention relates to a solid electrolyte material, a solid electrolyte, a method for manufacturing a solid electrolyte or an all-solid-state battery, wherein the solid electrolyte material is amorphous, contains lithium, tantalum, phosphorus and oxygen as constituent elements, and contains at least one element selected from boron, niobium, silicon and bismuth as a constituent element.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] A technical solution of the present invention relates to a solid electrolyte material, a solid electrolyte, a method for manufacturing a solid electrolyte, or an all-solid-state battery. Background Art

[0002] In recent years, there has been a demand for the development of high-output and high-capacity batteries as power sources for laptop computers, tablet terminals, mobile phones, smartphones, and electric vehicles (EVs). Among them, all-solid-state batteries that use solid electrolytes instead of liquid electrolytes such as organic solvents have attracted much attention as batteries with excellent charge and discharge efficiency, charging speed, safety, and productivity.

[0003] As the above-mentioned solid electrolyte, an inorganic solid electrolyte has attracted attention, and as the inorganic solid electrolyte, mainly oxide-based and sulfide-based solid electrolytes are known.

[0004] When using sulfide-based solid electrolytes, although there are advantages such as being able to produce batteries by cold pressing, etc., they are unstable relative to humidity and may produce harmful hydrogen sulfide gas. Therefore, oxide-based solid electrolytes are being developed from the perspective of safety and other aspects.

[0005] As such an oxide-based solid electrolyte, Non-Patent Document 1 states that LiTa2PO8 having a monoclinic crystal structure exhibits high lithium ion conductivity (total conductivity (25°C): 2.5×10 -4 S cm -1 ).

[0006] Prior Art Literature

[0007] Non-patented literature 1: J.Kim et al., J.Mater.Chem.A, 2018, 6, p22478-22482 Summary of the invention

[0008] Problems to be solved by the invention

[0009] The grain boundary resistance of oxide-based solid electrolytes is extremely high. In order to obtain ion conductivity that can be used in all-solid-state batteries, it is necessary not only to pressurize the solid electrolyte powder but also to make a high-density sintered body. In addition, in order to obtain such a high-density sintered body, it is necessary to sinter it at a high temperature of about 1100°C, for example.

[0010] In addition, when an oxide-based solid electrolyte is used to produce an all-solid-state battery, it is necessary to sinter it together with a positive electrode material, a negative electrode material, etc. in order to obtain high ion conductivity.

[0011] During these firing processes, in order to suppress the decomposition and deterioration of other materials such as the positive electrode and negative electrode materials in terms of economy or equipment, it is expected that a sintered body with high ion conductivity can be obtained even when the firing is carried out at a low temperature (for example, below 900°C). However, when LiTa2PO8 described in non-patent document 1 was fired at a low temperature, a sintered body showing sufficient ion conductivity was not obtained.

[0012] One aspect of the present invention provides a solid electrolyte material that can obtain a sintered body having sufficient ion conductivity even when sintered at a low temperature (for example, 900° C. or less).

[0013] Means for solving problems

[0014] The present inventors have conducted intensive studies and have found that the above-mentioned problems can be solved according to the following technical configuration examples, thereby completing the present invention.

[0015] The technical configuration examples of the present invention are as follows.

[0016] [1] A solid electrolyte material which is amorphous and contains lithium, tantalum, phosphorus and oxygen as constituent elements and contains at least one element selected from boron, niobium, silicon and bismuth as a constituent element.

[0017] [2] The solid electrolyte material according to [1], wherein the content of tantalum element is 10.6 to 16.6 atomic %.

[0018] [3] The solid electrolyte material according to [1] or [2], wherein the phosphorus content is 5.3 to 8.8 atomic %.

[0019] [4] The solid electrolyte material according to any one of [1] to [3], wherein the content of lithium element is 5.0 to 20.0 atomic %.

[0020] [5] The solid electrolyte material according to any one of [1] to [4], wherein the content of the boron element is 0.1 to 5.0 atomic %.

[0021] [6] The solid electrolyte material according to any one of [1] to [5], wherein the content of niobium element is 0.1 to 5.0 atomic %.

[0022] [7] The solid electrolyte material according to any one of [1] to [6], wherein the silicon content is 0.1 to 5.0 atomic %.

[0023] [8] The solid electrolyte material according to any one of [1] to [7], wherein the content of bismuth element is 0.1 to 5.0 atomic %.

[0024] [9] The solid electrolyte material according to any one of [1] to [8], comprising one or more elements selected from Zr, Ga, Sn, Hf, W, Mo, Al and Ge as constituent elements.

[0025]

[10] A solid electrolyte obtained by using the solid electrolyte material described in any one of [1] to [9].

[0026]

[11] A solid electrolyte which is a sintered body of the solid electrolyte material according to any one of [1] to [9].

[0027]

[12] A method for producing a solid electrolyte, comprising the step of calcining the solid electrolyte material described in any one of [1] to [9] at 500 to 900° C., wherein the solid electrolyte is the solid electrolyte described in

[10] or

[11] .

[0028]

[13] An all-solid-state battery comprising a positive electrode, a negative electrode and a solid electrolyte layer,

[0029] The positive electrode has a positive electrode active material,

[0030] The negative electrode has a negative electrode active material,

[0031] The solid electrolyte layer is located between the positive electrode and the negative electrode,

[0032] The solid electrolyte layer includes the solid electrolyte described in

[10] or

[11] .

[0033]

[14] According to the all-solid-state battery described in

[13] , the positive electrode active material comprises LiM3PO4 [M3 is one or more elements selected from Mn, Co, Ni, Fe, Al, Ti and V, or two elements of V and O], LiM5VO4 [M5 is one or more elements selected from Fe, Mn, Co, Ni, Al and Ti], Li2M6P2O7 [M6 is one or more elements selected from Fe, Mn, Co, Ni, Al, Ti and V, or two elements of V and O], LiVP2O7, Li x7 V y7 M7 z7 [2≤x7≤4, 1≤y7≤3, 0≤z7≤1, 1≤y7+z7≤3, M7 is one or more elements selected from Ti, Ge, Al, Ga and Zr], Li 1+x8 Al x8 M8 2-x8 (PO4)3[0≤x8≤0.8, M8 is one or more elements selected from Ti and Ge], LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2, LiCoO2, LiNiO2, LiMn2O4, Li2CoP2O7, Li3V2(PO4)3, Li3Fe2(PO4)3, LiNi 0.5 Mn 1.5 O4 and Li4Ti5O 12 One or more compounds in .

[0034]

[15] According to the all-solid-state battery described in

[13] or

[14] , the negative electrode active material comprises LiM3PO4 [M3 is one or more elements selected from Mn, Co, Ni, Fe, Al, Ti and V, or two elements of V and O], LiM5VO4 [M5 is one or more elements selected from Fe, Mn, Co, Ni, Al and Ti], Li2M6P2O7 [M6 is one or more elements selected from Fe, Mn, Co, Ni, Al, Ti and V, or two elements of V and O], LiVP2O7, Li x7 V y7 M7 z7 [2≤x7≤4, 1≤y7≤3, 0≤z7≤1, 1≤y7+z7≤3, M7 is one or more elements selected from Ti, Ge, Al, Ga and Zr], Li 1+x8 Al x8 M8 2-x8 (PO4)3[0≤x8≤0.8, M8 is one or more elements selected from Ti and Ge], (Li 3-a9x9+(5-b9)y9 M9 x9 )(V 1-y9 M10 y9 )O4[M9 is one or more elements selected from Mg, Al, Ga and Zn, M10 is one or more elements selected from Zn, Al, Ga, Si, Ge, P and Ti, 0≤x9≤1.0, 0≤y9≤0.6, a9 is the average valence of M9, b9 is the average valence of M10], LiNb2O7, Li4Ti5O 12 、Li4Ti5PO 12 , TiO2, LiSi and graphite.

[0035]

[16] The all-solid-state battery according to any one of

[13] to

[15] , wherein the positive electrode and the negative electrode contain the solid electrolyte described in

[10] or

[11] .

[0036] Effects of the Invention

[0037] According to one embodiment of the present invention, even if sintering is performed at a low temperature (e.g., below 900°C), a sintered body with sufficient ion conductivity, especially sufficient lithium ion conductivity, can be obtained. Therefore, by using the solid electrolyte material involved in one embodiment of the present invention, an all-solid battery can be easily produced that has excellent economic efficiency, suppresses decomposition or deterioration of other materials such as positive or negative electrode materials, and contains a solid electrolyte with sufficient ion conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is the XRD pattern of the solid electrolyte material obtained in Example 3.

[0039] Figure 2 This is the XRD pattern of the solid electrolyte material obtained in Example 27.

[0040] Figure 3 This is an XRD pattern of the solid electrolyte material obtained in Comparative Example 3.

[0041] Figure 4 This is the result of fitting the diffraction peak having the maximum intensity in the range of 20°≤2θ≤40° in the XRD pattern of the solid electrolyte material obtained in Example 3.

[0042] Figure 5 This is the result of fitting the diffraction peak having the maximum intensity in the range of 20°≤2θ≤40° in the XRD pattern of the solid electrolyte material obtained in Example 27.

[0043] Figure 6 This is the result of fitting the diffraction peak having the maximum intensity in the range of 20°≤2θ≤40° in the XRD pattern of the solid electrolyte material obtained in Comparative Example 3. DETAILED DESCRIPTION

[0044] 《Solid Electrolyte Materials》

[0045] A solid electrolyte material (hereinafter also referred to as “the present material”) according to one embodiment of the present invention is amorphous and contains lithium, tantalum, phosphorus and oxygen as constituent elements, and contains at least one element selected from boron, niobium, silicon and bismuth as a constituent element.

[0046] The present material is amorphous. The amorphous nature of the present material can be judged, for example, by the fact that no peak is observed in the X-ray diffraction (XRD) pattern (a broad peak can be observed), that is, the half-value width of the diffraction peak with the maximum intensity observed in the range of 20≤2θ≤40° is greater than 0.15°. In other words, when the half-value width of the diffraction peak is less than 0.15°, it is judged to be crystalline.

[0047] Since the present material is amorphous, a solid electrolyte obtained from the present material, particularly a solid electrolyte (sintered body) obtained by sintering the present material, tends to exhibit higher ion conductivity.

[0048] The shape and size of the material are not particularly limited, but are preferably in a particle (powder) state. The average particle size (D50) of the material is preferably 0.1 to 10 μm, more preferably 0.1 to 5 μm.

[0049] When the average particle size of the present material is within the above range, a solid electrolyte obtained from the present material, particularly a solid electrolyte (sintered body) obtained by sintering the present material, tends to exhibit higher ion conductivity.

[0050] The elements constituting the present material are not particularly limited as long as they contain lithium, tantalum, phosphorus and oxygen, and also contain at least one element selected from boron, niobium, silicon and bismuth. From the perspective of being able to lower the sintering temperature when obtaining a sintered body with sufficient ion conductivity, it is preferred to contain lithium, tantalum, phosphorus, boron and oxygen.

[0051] In addition, the present material may contain one or more elements selected from the group consisting of Zr, Ga, Sn, Hf, W, Mo, Al and Ge as elements constituting the present material.

[0052] The content of lithium element in the present material is preferably 5.0 to 20.0 atomic %, more preferably 9.0 to 15.0 atomic %, from the viewpoint of easily obtaining a solid electrolyte having higher lithium ion conductivity.

[0053] In addition, the content of each element in the present material, for example, as a lithium-containing transition metal oxide such as LiCoO2, a standard powder sample containing Mn, Co, and Ni in a ratio of 1:1:1 is used, and the absolute intensity quantitative method of Auger electron spectroscopy (AES: Auger Electron Spectroscopy) is used for determination. In addition, it can also be obtained by quantitative analysis known in the past. For example, after adding acid to the sample for thermal decomposition, the thermal decomposition product can be constant in volume, and a high-frequency inductively coupled plasma (ICP) luminescence analysis device can be used to obtain the content of each element in the present material.

[0054] The content of tantalum in the present material is preferably 10.6 to 16.6 atomic %, more preferably 11.0 to 16.0 atomic %, from the viewpoint of easily obtaining a solid electrolyte having a higher lithium ion conductivity.

[0055] The content of phosphorus in the present material is preferably 5.3 to 8.8 atomic %, more preferably 5.8 to 8.3 atomic %, from the viewpoint of easily obtaining a solid electrolyte having a higher lithium ion conductivity.

[0056] When the present material contains boron, the content of boron in the present material is preferably 0.1 to 5.0 atomic %, more preferably 0.5 to 3.0 atomic % from the viewpoint of lowering the firing temperature when obtaining a sintered body having sufficient ion conductivity.

[0057] When the present material contains niobium, the content of niobium in the present material is preferably 0.1 to 5.0 atomic %, more preferably 0.5 to 3.0 atomic %, from the viewpoint of lowering the firing temperature when obtaining a sintered body having sufficient ion conductivity.

[0058] When the present material contains silicon, the content of silicon in the present material is preferably 0.1 to 5.0 atomic %, more preferably 0.5 to 3.0 atomic % from the viewpoint of lowering the firing temperature when obtaining a sintered body having sufficient ion conductivity.

[0059] When the present material contains bismuth element, the content of bismuth element in the present material is preferably 0.1 to 5.0 atomic %, more preferably 0.1 to 2.0 atomic % from the viewpoint of lowering the firing temperature when obtaining a sintered body having sufficient ion conductivity.

[0060] When the present material contains one or more elements selected from Zr, Ga, Sn, Hf, W, Mo, Al and Ge, the content of each of these elements in the present material is preferably 0.1 to 5.0 atomic %, and more preferably 0.1 to 3.0 atomic %, from the perspective of having a tendency to easily obtain a solid electrolyte exhibiting higher ion conductivity.

[0061] <Manufacturing method of this material>

[0062] For example, the present material can be manufactured as a component (Z) containing lithium, tantalum, phosphorus and oxygen as constituent elements and at least one element selected from boron, niobium, silicon and bismuth as a constituent element by a method (I) comprising a pulverizing step of pulverizing a pulverizing material containing lithium, tantalum, phosphorus and oxygen as constituent elements and at least one element selected from boron, niobium, silicon and bismuth as a constituent element.

[0063] In the above-mentioned pulverization step, it is preferable to pulverize and mix so that the obtained present material becomes amorphous by a mechanochemical reaction. In this case, it is preferable to pulverize and mix so that the average particle size of the present material falls within the above-mentioned range.

[0064] As the above-mentioned pulverizing step, for example, a method of pulverizing using a rolling mill, a ball mill, a small-diameter ball mill (bead mill), a medium stirring mill, a jet mill, a mortar, an automatic mixing mortar, a tank decomposer, a jet mill, etc. can be cited. Among them, from the perspective of being able to easily obtain a solid electrolyte that exerts higher ion conductivity when a solid electrolyte is obtained from the present material, a method of pulverizing using a ball mill or a bead mill is preferred, and a method of pulverizing using a ball mill with a ball having a diameter of 0.1 to 10 mm is more preferred.

[0065] The time of the pulverization step is preferably 0.5 to 48 hours, more preferably 2 to 48 hours, from the viewpoint of easily obtaining the amorphous material having an average particle size within the above range.

[0066] In the pulverizing step, the pulverizing and mixing may be performed while heating as necessary, but the pulverizing and mixing are usually performed at room temperature.

[0067] The pulverization step may be performed in the air, preferably in an atmosphere of nitrogen and / or argon with an oxygen content adjusted to a range of 0 to 20% by volume.

[0068] From the viewpoint of easy handling, the raw material used for the material to be pulverized is preferably an inorganic compound.

[0069] The raw materials may be produced by conventionally known methods, or commercially available products may be used.

[0070] As the above method (I), for example:

[0071] Method (i) using as the above-mentioned pulverization object material a compound containing a lithium atom, a compound containing a tantalum atom, a compound containing a phosphorus atom, and at least one compound selected from a compound containing a boron atom, a compound containing a niobium atom, a compound containing a silicon atom, and a compound containing a bismuth atom.

[0072] As compounds containing lithium atoms, for example, lithium carbonate (Li2CO3), lithium oxide (Li2O), lithium hydroxide (LiOH), lithium acetate (LiCH3COO) and hydrates thereof can be cited. Among them, lithium carbonate, lithium hydroxide and lithium acetate are preferred from the perspective of easy decomposition and reaction.

[0073] The lithium atom-containing compound may be used alone or in combination of two or more.

[0074] Examples of the tantalum atom-containing compound include tantalum pentoxide (Ta2O5) and tantalum nitrate (Ta(NO3)5). Among them, tantalum pentoxide is preferred from the perspective of cost.

[0075] The tantalum atom-containing compound may be used alone or in combination of two or more.

[0076] As the compound containing a phosphorus atom, phosphate is preferred. As the phosphate, from the viewpoint of easy decomposition and reaction, for example, diammonium hydrogen phosphate ((NH4)2HPO4) and monoammonium dihydrogen phosphate (NH4H2PO4) can be mentioned.

[0077] The phosphorus atom-containing compound may be used alone or in combination of two or more.

[0078] Examples of compounds containing boron atoms include LiBO2, LiB3O5, Li2B4O7, Li3B 11 O 18 、Li3BO3、Li3B7O 12 、Li4B2O5、Li6B4O9、Li 3-x5 B 1-x5 C x5 O3(0<x5<1), Li 4-x6 B 2-x6 C x6 O5(0<x6<2), Li 2.4 Al 0.2 BO3, Li 2.7 Al 0.1 BO3, B2O3, H3BO3.

[0079] The boron atom-containing compound may be used alone or in combination of two or more.

[0080] Examples of compounds containing niobium atoms include Nb2O5, LiNbO3, LiNb3O8, and NbPO5.

[0081] The niobium atom-containing compound may be used alone or in combination of two or more.

[0082] Examples of compounds containing silicon atoms include SiO2, Li2SiO3, Li2Si2O5, Li2Si3O7, Li4SiO4, Li6Si2O7, and Li8SiO6.

[0083] The silicon atom-containing compound may be used alone or in combination of two or more.

[0084] Examples of compounds containing bismuth atoms include LiBiO2, Li3BiO3, Li4Bi2O5, Li 2.4 Al 0.2 BiO3, Bi2O3.

[0085] The bismuth atom-containing compound may be used alone or in combination of two or more.

[0086] In the case where the present material contains one or more elements M1 selected from Zr, Ga, Sn, Hf, W and Mo, and / or contains one or more elements M2 selected from Al and Ge, a method (i') can be cited in which a compound containing a lithium atom, a compound containing a tantalum atom, a compound containing a phosphorus atom, at least one compound selected from a compound containing a boron atom, a compound containing a niobium atom, a silicon atom and a bismuth atom, and a compound containing the element M1 and / or a compound containing the element M2 are used as the above-mentioned pulverization object material.

[0087] The compound containing the element M1 is not particularly limited, but is preferably an inorganic compound from the viewpoint of easy handling, and examples thereof include oxides and nitrates of M1. Among them, oxides are preferred from the viewpoint of cost.

[0088] The compound containing M1 may be used alone or in combination of two or more.

[0089] When M1 is Ga or Sn, examples of the oxide include gallium oxide (Ga2O3), tin oxide (SnO2), and the like.

[0090] When M1 is Zr, Hf, W or Mo, the oxides include zirconium oxide (ZrO2), hafnium oxide (HfO2), tungsten oxide (WO3), molybdenum oxide (MoO3), etc. When M1 is Zr, Hf, W or Mo, in addition to the oxides, zirconium hydroxide (Zr(OH)4), hafnium hydroxide (Hf(OH)4), tungstic acid (H2WO4), molybdic acid (H2MoO4) may also be used from the perspective of easy reaction.

[0091] The compound containing the element M2 is not particularly limited, but is preferably an inorganic compound from the viewpoint of easy handling, and examples thereof include oxides of M2.

[0092] The compound containing the element M2 may be used alone or in combination of two or more.

[0093] When M2 is Ge or Al, examples of the oxide include germanium oxide (GeO2), aluminum oxide (Al2O3), and the like.

[0094] The mixing ratio of the raw materials may be such that the content of each constituent element in the obtained present material falls within the above-mentioned range, for example.

[0095] In the calcination step described later, since lithium atoms are likely to flow out of the system, the lithium atom-containing compound may be used in an excess of about 10% to 20%.

[0096] In order to suppress the generation of by-products in the calcination step described later, the phosphorus atom-containing compound may be used in an excess of about 0.1 to 10%.

[0097] In the method (i) and the method (i'), the raw materials may be mixed before the pulverizing step, but preferably, the raw materials are mixed while being pulverized (pulverization and mixing) in the pulverizing step.

[0098] In addition, as the above-mentioned method (I), for example:

[0099] (ii) a method in which a compound (a) containing lithium, tantalum, phosphorus and oxygen as constituent elements and at least one compound (b) selected from a boron compound, a niobium compound, a silicon compound and a bismuth compound are used as the pulverization target material; or

[0100] Method (iii) using, as the pulverization target material, a compound (c) containing lithium, tantalum, phosphorus and oxygen as constituent elements and containing at least one element selected from boron, niobium, silicon and bismuth as a constituent element.

[0101] In addition, in methods (ii) and (iii), a compound containing element M1 and / or a compound containing element M2 may be further used.

[0102] In the method (ii), the compound (a) and the compound (b) may be mixed before the pulverizing step, but preferably, the compound (a) and the compound (b) are mixed while being pulverized (pulverization and mixing) in the pulverizing step.

[0103] Compound (a)

[0104] The compound (a) is a compound containing lithium, tantalum, phosphorus, and oxygen as constituent elements, and is preferably an oxide containing these elements, and more preferably a lithium ion conductive compound containing these elements.

[0105] The compound (a) used in the method (ii) may be one kind or two or more kinds.

[0106] Compound (a) is preferably a compound having a monoclinic crystal structure. Whether compound (a) has a monoclinic crystal structure can be determined, for example, by performing a Rietveld analysis on the X-ray diffraction (XRD) pattern of compound (a), and specifically by using the method of the following embodiment.

[0107] As compound (a), specifically, there can be mentioned compounds (a1) containing lithium, tantalum, phosphorus and oxygen as constituent elements and further containing one or more elements M1 selected from Zr, Ga, Sn, Hf, W and Mo, compounds (a2) containing lithium, tantalum, phosphorus and oxygen as constituent elements and further containing one or more elements M2 selected from Al and Ge, etc. Among them, from the perspective of further exerting the effects of the present invention, as compound (a), preferably, the constituent elements are only composed of lithium, tantalum, phosphorus and oxygen, and more preferably LiTa2PO8.

[0108] The compound (a1) is preferably LiTa2PO8, or a compound in which a portion of Ta in LiTa2PO8 is replaced by an element M1, and preferably has a monoclinic structure.

[0109] Specifically, the compound (a1) is preferably composed of the formula Li 1+(5-a)x 〕Ta 2-x M1 x A compound represented by PO8 [M1 is one or more elements selected from Zr, Ga, Sn, Hf, W and Mo, 0.0≤x<1.0, a is the average valence of M1].

[0110] In the solid electrolyte obtained using the compound (a), M1 is more preferably W or Mo, and even more preferably W, from the viewpoint of improving the lithium ion conductivity at the grain boundary.

[0111] The above-mentioned x is preferably 0.95 or less, more preferably 0.90 or less, further preferably 0.85 or less, more preferably 0.80 or less, and particularly preferably 0.75 or less.

[0112] When x is within the above range, in the solid electrolyte obtained using the compound (a), the lithium ion conductivity at the grain boundaries tends to be improved.

[0113] According to the valence and content of M1, the amount of Li varies corresponding to the average valence of M1 to obtain the charge neutrality of the above compound (a). The average valence represented by the above a can be calculated as follows. In the case where M1 is composed of two or more elements, the above a is calculated by weighted average using the valence of each element and the content of each element. For example, in the case where M1 is composed of 80 atomic % Nb and 20 atomic % Zr, a is calculated as (+5×0.8)+(+4×0.2)=+4.8. In addition, in the case where M1 is composed of 80 atomic % Nb and 20 atomic % W, a is calculated as (+5×0.8)+(+6×0.2)=+5.2.

[0114] The above-mentioned compound (a2) is preferably LiTa2PO8, or a compound in which a part of P in LiTa2PO8 is replaced by element M2, and preferably has a monoclinic structure.

[0115] Specifically, the compound (a2) is preferably composed of the formula Li 1+(5-b)y 〕Ta2P 1-y M2 y A compound represented by O8 [M2 is one or more elements selected from Al and Ge, 0.0≤y<0.7, b is the average valence of M2].

[0116] In the solid electrolyte obtained using the compound (a), M2 is more preferably Al from the viewpoint of improving the lithium ion conductivity at the grain boundary.

[0117] The above-mentioned y is preferably 0.65 or less, more preferably 0.60 or less, and further preferably 0.55 or less.

[0118] When y is within the above range, in the solid electrolyte obtained using the compound (a), the total conductivity, which is the sum of the lithium ion conductivity within the crystal grains and at the crystal grain boundaries, tends to be improved.

[0119] The average price represented by b can be calculated in the same way as the method of calculating the average price a.

[0120] The method for producing the compound (a) is not particularly limited, and conventionally known production methods such as solid phase reaction and liquid phase reaction can be used. Specific examples of the production method include a method comprising at least one mixing step and one calcining step.

[0121] As a mixing step in the method for producing the above-mentioned compound (a), for example, there can be mentioned a step of mixing compounds containing lithium atoms (for example, oxides, carbonates), compounds containing tantalum atoms (for example, oxides, nitrates), compounds containing phosphorus atoms (for example, ammonium salts), and compounds containing element M1 (for example, oxides) and / or compounds containing element M2 (for example, oxides) as raw materials.

[0122] The above raw materials may be used alone or in combination of two or more.

[0123] Examples of a method for mixing the raw materials include a method of mixing using a roll mill, a ball mill, a small diameter ball mill (bead mill), a medium stirring mill, a jet mill, a mortar, an automatic mixing mortar, a tank disintegrator, a jet mill, and the like.

[0124] The mixing ratio of the raw materials may be, for example, a stoichiometric ratio that can give a desired composition of the compound (a).

[0125] In addition, in the calcination step described later, since lithium atoms are easy to flow out of the system, the above-mentioned lithium atom-containing compound can be used in excess of about 10% to 20%. In addition, in the calcination step described later, in order to suppress the generation of by-products, the above-mentioned phosphorus atom-containing compound can be used in excess of about 0.10% to 10%.

[0126] During the mixing, the mixture may be mixed while being heated as necessary, but is usually mixed at room temperature.

[0127] The mixing may be performed in the air, but is preferably performed in an atmosphere of nitrogen and / or argon gas whose oxygen content is adjusted to a range of 0 to 20% by volume.

[0128] In the calcining process of the manufacturing method of the above-mentioned compound (a), the mixture obtained in the mixing process is calcined. In the case of performing multiple calcining processes, in order to crush or reduce the particle size of the calcined product obtained in the calcining process, a pulverizing process using a ball mill or a mortar or the like can be provided. In particular, the reaction rate of the phase generation of the compound (a) is slow, so sometimes a reaction intermediate is present in the first calcining. In this case, it is preferred to perform the first calcining and then perform the calcining process after performing the pulverizing process.

[0129] The calcining step may be performed in the air, but is preferably performed in an atmosphere of nitrogen and / or argon gas whose oxygen content is adjusted to a range of 0 to 20% by volume.

[0130] The calcination temperature varies depending on the calcination time, but is preferably 800 to 1200°C, more preferably 950 to 1100°C, and even more preferably 950 to 1000°C.

[0131] When the calcination temperature is within the above range, lithium atoms are less likely to flow out of the system, and a compound (a) having high ion conductivity tends to be easily obtained.

[0132] The firing time (the total firing time when the firing step is performed several times) varies depending on the firing temperature, but is preferably 1 to 16 hours, and more preferably 3 to 12 hours.

[0133] When the calcination time is within the above range, lithium atoms are less likely to flow out of the system, and a compound having high ion conductivity tends to be easily obtained.

[0134] The fired product obtained after the firing step may absorb moisture or react with carbon dioxide to deteriorate if left in the air. Therefore, the fired product obtained after the firing step is preferably transferred to a dehumidified inert gas atmosphere for storage when the temperature reaches 200° C. or less during the temperature drop after the firing step.

[0135] Compound (b)

[0136] The compound (b) is at least one compound selected from the group consisting of boron compounds, niobium compounds, silicon compounds and bismuth compounds. Among them, boron compounds and niobium compounds are preferred, and boron compounds are more preferred, in terms of further exerting the effects of the present invention.

[0137] In addition, compound (b) is a compound different from compound (a).

[0138] The compound (b) used in the method (ii) may be one kind or two or more kinds.

[0139] From the viewpoint of easy handling, the compound (b) is preferably an inorganic compound, more preferably a compound containing lithium or hydrogen as a constituent element, and still more preferably a composite oxide containing lithium as a constituent element.

[0140] The compound (b) can be produced by a conventionally known method, or a commercially available product can be used.

[0141] Compound (b) is preferably a crystalline compound. Whether compound (b) is a crystalline compound can be determined, for example, from the X-ray diffraction (XRD) pattern of compound (b).

[0142] Examples of boron compounds include LiBO2, LiB3O5, Li2B4O7, Li3B 11 O 18 、Li3BO3、Li3B7O 12 、Li4B2O5、Li6B4O9、Li 3-x5 B 1-x5 C x5 O3(0<x5<1), Li 4-x6 B 2-x6 C x6 O5(0<x6<2), Li 2.4 Al 0.2 BO3, Li 2.7 Al 0.1 BO3, B2O3, H3BO3.

[0143] Examples of niobium compounds include Nb2O5, LiNbO3, LiNb3O8, and NbPO5.

[0144] Examples of silicon compounds include SiO2, Li2SiO3, Li2Si2O5, Li2Si3O7, Li4SiO4, Li6Si2O7, and Li8SiO6.

[0145] Examples of bismuth compounds include LiBiO2, Li3BiO3, Li4Bi2O5, Li2.4 Al 0.2 BiO3, Bi2O3.

[0146] The method for producing the compound (b) is not particularly limited, and for example, a conventionally known production method such as a solid phase reaction or a liquid phase reaction can be used. Specific examples of the production method include a method comprising a mixing step and a calcining step.

[0147] In addition, as the compound (b), a commercially available product can be used.

[0148] Mixing process

[0149] As the mixing step, for example, when producing a composite oxide containing lithium as a constituent element, a lithium atom-containing compound as a raw material is mixed with a boron atom-containing compound, a niobium atom-containing compound, a silicon atom-containing compound or a bismuth atom-containing compound.

[0150] Depending on the type of compound (b), this mixing step may not be performed.

[0151] The compound containing lithium atoms is not particularly limited, but is preferably an inorganic compound from the perspective of easy handling. Examples of inorganic compounds containing lithium atoms include lithium carbonate (Li2CO3), lithium oxide (Li2O), lithium hydroxide (LiOH), lithium acetate (LiCH3COO), and hydrates thereof. Among them, lithium carbonate is preferred from the perspective of easy decomposition and reaction. In addition, lithium hydroxide monohydrate (LiOH·H2O) is also preferably used.

[0152] The lithium atom-containing compound may be used alone or in combination of two or more.

[0153] The compound containing a boron atom is not particularly limited, but is preferably an inorganic compound from the viewpoint of easy handling, and examples of the inorganic compound containing a boron atom include boric acid (H3BO3) and boron oxide (B2O3). Among them, boric acid is preferred.

[0154] The boron atom-containing compound may be used alone or in combination of two or more.

[0155] Examples of compounds containing niobium atoms include Nb2O5, LiNbO3, LiNb3O8, and NbPO5.

[0156] The niobium atom-containing compound may be used alone or in combination of two or more.

[0157] Examples of compounds containing silicon atoms include SiO2, Li2SiO3, Li2Si2O5, Li2Si3O7, Li4SiO4, Li6Si2O7, and Li8SiO6.

[0158] The silicon atom-containing compound may be used alone or in combination of two or more.

[0159] The compound containing bismuth atoms is not particularly limited, but is preferably an inorganic compound from the viewpoint of easy handling, and examples of inorganic compounds containing bismuth atoms include bismuth oxide and bismuth nitrate (Bi(NO3)3). Among them, bismuth oxide is preferred.

[0160] The bismuth atom-containing compound may be used alone or in combination of two or more.

[0161] Examples of a method for mixing the raw materials include a method of mixing using a roll mill, a ball mill, a small diameter ball mill (bead mill), a medium stirring mill, a jet mill, a mortar, an automatic mixing mortar, a tank disintegrator, a jet mill, and the like.

[0162] The mixing ratio of the raw materials may be, for example, a stoichiometric ratio that can give a desired composition of the compound (b).

[0163] In the calcination step described later, since lithium atoms are likely to flow out of the system, the lithium atom-containing compound may be used in an excess of about 10% to 20%.

[0164] During the mixing, the mixture may be mixed while being heated as necessary, but is usually mixed at room temperature.

[0165] The mixing may be performed in the air, but is preferably performed in an atmosphere of nitrogen and / or argon gas whose oxygen content is adjusted to a range of 0 to 20% by volume.

[0166] ·Firing process

[0167] In the calcining step, the mixture obtained in the mixing step is calcined. When the calcining step is performed multiple times, a pulverizing step using a ball mill, a mortar or the like may be provided in order to pulverize or reduce the particle size of the calcined product obtained in the calcining step.

[0168] The calcining step may be performed in the air, but is preferably performed in an atmosphere of nitrogen and / or argon gas whose oxygen content is adjusted to a range of 0 to 20% by volume.

[0169] The calcination temperature varies depending on the calcination time, but is preferably 400 to 1000°C, more preferably 500 to 900°C.

[0170] When the calcination temperature is within the above range, lithium atoms are less likely to flow out of the system, and the desired compound (b) tends to be easily obtained.

[0171] The firing time (the total firing time when the firing step is performed several times) varies depending on the firing temperature, but is preferably 1 to 48 hours, and more preferably 3 to 24 hours.

[0172] When the calcination time is within the above range, lithium atoms are less likely to flow out of the system, and the desired compound (b) tends to be easily obtained.

[0173] The fired product obtained after the firing step may absorb moisture or react with carbon dioxide to deteriorate if left in the air. Therefore, the fired product obtained after the firing step is preferably transferred to a dehumidified inert gas atmosphere for storage when the temperature reaches 200° C. or less during the temperature drop after the firing step.

[0174] In the method (ii), the compound (a) and the compound (b) are preferably used in such an amount that the content of each constituent element in the obtained present material falls within the above-mentioned range.

[0175] Compound (c)

[0176] The compound (c) is a compound containing lithium, tantalum, phosphorus and oxygen as constituent elements and containing at least one element selected from boron, niobium, silicon and bismuth, and is preferably an oxide containing these elements, and more preferably a lithium ion conductive compound containing these elements.

[0177] The compound (c) may contain one or more elements selected from the group consisting of Zr, Ga, Sn, Hf, W, Mo, Al and Ge.

[0178] Compound (c) is preferably a compound having a monoclinic crystal structure. Whether compound (c) has a monoclinic crystal structure can be determined, for example, by Rietveld analysis of the X-ray diffraction (XRD) pattern of compound (c), specifically, by the method of the following example.

[0179] The method for producing the compound (c) is not particularly limited, and conventionally known production methods such as solid phase reaction and liquid phase reaction can be used. Specific examples of the production method include a method comprising at least one mixing step and one calcining step, respectively.

[0180] As a mixing step in the method for producing the compound (c), for example, there can be mentioned a step of mixing a lithium atom-containing compound (e.g., oxide, hydroxide, carbonate), a tantalum atom-containing compound (e.g., oxide, nitrate), a phosphorus atom-containing compound (e.g., ammonium salt), and at least one compound selected from a boron atom-containing compound (e.g., oxide), a niobium atom-containing compound (e.g., oxide, nitrate), a silicon atom-containing compound (e.g., oxide), and a bismuth atom-containing compound (e.g., oxide). As the boron atom-containing compound, the niobium atom-containing compound, the silicon atom-containing compound, and the bismuth atom-containing compound, the compound (b) can be used respectively. As the boron atom-containing compound, the niobium atom-containing compound, the silicon atom-containing compound, and the bismuth atom-containing compound, the boron atom-containing compound and the niobium atom-containing compound are preferred from the viewpoint of further exerting the effects of the present invention.

[0181] The above raw materials may be used alone or in combination of two or more.

[0182] The mixing ratio of the raw materials may be such that the content of each constituent element in the obtained present material can fall within the above-mentioned range, for example.

[0183] In addition, in the calcination step described later, since lithium atoms are easy to flow out of the system, the above-mentioned lithium atom-containing compound can be used in excess of about 10% to 20%. In addition, in the calcination step described later, in order to suppress the generation of by-products, the above-mentioned phosphorus atom-containing compound can be used in excess of about 0.10%.

[0184] Examples of the method for mixing the raw materials and the conditions (temperature, atmosphere, etc.) during the mixing process include the same methods and conditions as those in the mixing step for producing the compound (a).

[0185] In the calcining step of the method for producing the compound (c), the mixture obtained in the mixing step is calcined. When the calcining step is performed multiple times, a pulverizing step using a ball mill or a mortar or the like may be provided in order to crush or reduce the particle size of the calcined product obtained in the calcining step. However, unlike the case of producing the compound (a), the reaction rate of the phase generation of the compound (c) is fast, and the desired compound (c) can be produced by a single calcining step, so it is preferred to produce the compound (c) by a single calcining step.

[0186] As the conditions (temperature, time, atmosphere, etc.) in the above-mentioned calcination step, for example, the same conditions as those in the calcination step when manufacturing the above-mentioned compound (a) can be cited. In addition, based on the same reasons as when manufacturing compound (a), the calcined product obtained after the calcination step is preferably transferred to a dehumidified inert gas atmosphere for storage, similarly to when manufacturing compound (a).

[0187] Solid Electrolytes

[0188] A solid electrolyte according to an embodiment of the present invention (hereinafter also referred to as “present electrolyte”) is obtained using the present material described above, and is preferably a sintered body of the present material obtained by sintering the present material.

[0189] The total ion conductivity of the sintered body of the present material obtained by sintering the present material at 850°C or higher and 900°C or lower is preferably 2.00×10 -4 S cm -1 More preferably, 3.00×10 -4 S cm -1 above.

[0190] The total ion conductivity of the sintered body of the present material obtained by sintering the present material at 750°C or higher and lower than 850°C is preferably 1.00×10 -5 S cm -1 More preferably, 5.00×10 -5 S cm -1 above.

[0191] The total ion conductivity of the sintered body of the present material obtained by sintering the present material at 700°C or higher and lower than 750°C is preferably 1.00×10 -5 S cm -1 More preferably, 2.00×10 -5 S cm -1 above.

[0192] The total ion conductivity of the sintered body of the present material obtained by sintering the present material at 650°C or higher and lower than 700°C is preferably 1.00×10 -6 S cm -1 More preferably, 2.00×10 -6 S cm -1 above.

[0193] When the total ion conductivity is within the above range, it can be said that a sintered body obtained by sintering the present material at a low temperature has sufficient ion conductivity.

[0194] The total ion conductivity can be specifically measured by the method described in the following examples.

[0195] <Method for producing the present electrolyte>

[0196] The method for producing the present electrolyte preferably includes a step A of sintering the present material, and more preferably a method of forming the present material and then sintering it to obtain a sintered body.

[0197] The calcination temperature in the step A is preferably 500 to 900°C, more preferably 600 to 900°C, and even more preferably 650 to 900°C.

[0198] Since this material is used, a sintered body having sufficient ion conductivity can be obtained even when sintering is performed at such a low temperature.

[0199] The calcination time in the step A varies depending on the calcination temperature, but is preferably 12 to 144 hours, and more preferably 48 to 96 hours.

[0200] When the calcination time is within the above range, a sintered body having sufficient ion conductivity can be obtained even when calcination is performed at a low temperature.

[0201] The calcination in the step A may be performed in the air, but is preferably performed in an atmosphere of nitrogen and / or argon with the oxygen content adjusted to a range of 0 to 20% by volume.

[0202] In addition, the calcination in the above step A can also be performed under a reducing gas atmosphere such as a nitrogen-hydrogen mixed gas containing a reducing gas such as hydrogen. The ratio of hydrogen contained in the nitrogen-hydrogen mixed gas can be, for example, 1 to 10% by volume. As the reducing gas, in addition to hydrogen, ammonia gas, carbon monoxide gas, etc. can also be used.

[0203] In the above step A, from the viewpoint of being able to easily obtain a solid electrolyte (sintered body) with higher ion conductivity, it is preferred to sinter a body obtained by molding the present material, and it is more preferred to sinter a body obtained by press molding the present material.

[0204] The pressure during press molding of the present material is not particularly limited, but is preferably 50 to 500 MPa, more preferably 100 to 400 MPa.

[0205] The shape of the molded body obtained by press-molding the present material is not particularly limited, but is preferably a shape corresponding to the use of the sintered body (solid electrolyte) obtained by sintering the molded body.

[0206] In addition, when manufacturing the present electrolyte, other components other than the present material may also be used. As the other components, the previously known materials used in the solid electrolyte of the all-solid battery may be cited, for example, as the lithium ion conductive compound, the lithium ion conductive materials having structures such as NASICON type and LISICON type may be cited.

[0207] The above-mentioned other components may be used alone or in combination of two or more.

[0208] The amount of the other components used is preferably 50% by mass or less, more preferably 30% by mass or less, based on 100% by mass of the total amount of the other components and the present material. It is preferred that the other components are not used.

[0209] All-solid-state battery

[0210] An all-solid-state battery (hereinafter also referred to as "the present battery") involved in one embodiment of the present invention comprises a positive electrode having a positive electrode active material, a negative electrode having a negative electrode active material, and a solid electrolyte layer located between the positive electrode and the negative electrode, wherein the solid electrolyte layer comprises the present electrolyte.

[0211] The present battery may be a primary battery or a secondary battery, but is preferably a secondary battery, and more preferably a lithium ion secondary battery, from the viewpoint of further exerting the effects of the present invention.

[0212] The structure of the present battery is not particularly limited as long as it includes a positive electrode, a negative electrode, and a solid electrolyte layer located between the positive electrode and the negative electrode, and may be any of a so-called thin film type, a laminated type, and a bulk type.

[0213] <Solid electrolyte layer>

[0214] The solid electrolyte layer is not particularly limited as long as it contains the present electrolyte, and may contain conventionally known additives used in the solid electrolyte layer of an all-solid-state battery as necessary, but is preferably composed of the present electrolyte.

[0215] The thickness of the solid electrolyte layer can be appropriately selected depending on the structure of the battery to be formed (thin film type, etc.), and is preferably 50 nm to 1000 μm, and more preferably 100 nm to 100 μm.

[0216] <Positive electrode>

[0217] The positive electrode is not particularly limited as long as it has a positive electrode active material, but preferably, a positive electrode having a positive electrode collector and a positive electrode active material layer is used.

[0218] [Positive electrode active material layer]

[0219] The positive electrode active material layer is not particularly limited as long as it contains a positive electrode active material, but preferably contains a positive electrode active material and a solid electrolyte, and may further contain additives such as a conductive aid and a sintering aid.

[0220] The thickness of the positive electrode active material layer can be appropriately selected depending on the structure of the battery to be formed (thin film type, etc.), and is preferably 10 to 200 μm, more preferably 30 to 150 μm, and further preferably 50 to 100 μm.

[0221] Positive active material

[0222] Examples of positive electrode active materials include LiCo oxide, LiNiCo oxide, LiNiCoMn oxide, LiNiMn oxide, LiMn oxide, LiMn spinel, LiMnNi oxide, LiMnAl oxide, LiMnMg oxide, LiMnCo oxide, LiMnFe oxide, LiMnZn oxide, LiCrNiMn oxide, LiCrMn oxide, lithium titanate, lithium metal phosphate, transition metal oxides, titanium sulfide, graphite, hard carbon, lithium nitride containing transition metals, silicon oxide, lithium silicate, lithium metal, lithium alloy, solid solution containing Li, and lithium storage metal compounds.

[0223] Among them, LiNiCoMn oxide, LiNiCo oxide, and LiCo oxide are preferred, and LiNiCoMn oxide is more preferred, from the perspectives of good affinity with solid electrolytes, excellent balance among macroscopic conductivity, microscopic conductivity and ionic conductivity, high average potential, and the ability to improve energy density or battery capacity in a balance between specific capacity and stability.

[0224] Alternatively, the positive electrode active material may be surface-coated with lithium niobate, lithium phosphate, lithium borate, or the like, which is an ion-conductive oxide.

[0225] The positive electrode active material used in the positive electrode active material layer may be one kind or two or more kinds.

[0226] Preferred examples of the positive electrode active material include LiM3PO4 [M3 is one or more elements selected from Mn, Co, Ni, Fe, Al, Ti and V, or two elements of V and O], LiM5VO4 [M5 is one or more elements selected from Fe, Mn, Co, Ni, Al and Ti], Li2M6P2O7 [M6 is one or more elements selected from Fe, Mn, Co, Ni, Al, Ti and V, or two elements of V and O], LiVP2O7, Li x7 V y7 M7 z7[2≤x7≤4, 1≤y7≤3, 0≤z7≤1, 1≤y7+z7≤3, M7 is one or more elements selected from Ti, Ge, Al, Ga and Zr], Li 1+x8 Al x8 M8 2-x8 (PO4)3[0≤x8≤0.8, M8 is one or more elements selected from Ti and Ge], LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiCoO2, LiNiO2, LiMn2O4, Li2CoP2O7, Li3V2(PO4)3, Li3Fe2(PO4)3, LiNi 0.5 Mn 1.5 O4、Li4Ti5O 12 .

[0227] The positive electrode active material is preferably in a particle form, and the 50% diameter in the volume-based particle size distribution is preferably 0.1 to 30 μm, more preferably 0.3 to 20 μm, further preferably 0.4 to 10 μm, and particularly preferably 0.5 to 3 μm.

[0228] The ratio of the major axis length to the minor axis length (major axis length / minor axis length) of the positive electrode active material, that is, the aspect ratio, is preferably less than 3, and more preferably less than 2.

[0229] The positive electrode active material may be in the form of secondary particles. In this case, the 50% diameter in the number-based particle size distribution of the primary particles is preferably 0.1 to 20 μm, more preferably 0.3 to 15 μm, further preferably 0.4 to 10 μm, and particularly preferably 0.5 to 2 μm.

[0230] The content of the positive electrode active material in the positive electrode active material layer is preferably 20 to 80% by volume, more preferably 30 to 70% by volume.

[0231] When the content of the positive electrode active material is within the above range, the positive electrode active material functions well, and there is a tendency that a battery with high energy density can be easily obtained.

[0232] Solid electrolyte

[0233] The solid electrolyte that can be used in the positive electrode active material layer is not particularly limited, and any conventionally known solid electrolyte can be used. However, the present electrolyte is preferably used from the viewpoint of further exerting the effects of the present invention.

[0234] The solid electrolyte used in the positive electrode active material layer may be one kind or two or more kinds.

[0235] ·additive

[0236] Preferred examples of the conductive additive include metal materials such as Ag, Au, Pd, Pt, Cu, and Sn, and carbon materials such as acetylene black, Ketjen black, carbon nanotubes, and carbon nanofibers.

[0237] As the sintering aid, the same compounds as the above-mentioned compound (b) are preferred.

[0238] The additives used in the positive electrode active material layer may be one kind or two or more kinds.

[0239] Positive electrode collector

[0240] The positive electrode current collector is not particularly limited as long as its material is a material that conducts electrons without inducing an electrochemical reaction. As the material of the positive electrode current collector, for example, conductive metal oxides such as copper, aluminum, and iron, alloys containing these metals, antimony-doped tin oxide (ATO), and tin-doped indium oxide (ITO) can be cited.

[0241] In addition, as the positive electrode current collector, a current collector having a conductive adhesive layer provided on the surface of the current collector may be used. Examples of the conductive adhesive layer include a layer containing a granular conductive material or a fibrous conductive material.

[0242] <Negative electrode>

[0243] The negative electrode is not particularly limited as long as it has a negative electrode active material, but preferably, a negative electrode has a negative electrode collector and a negative electrode active material layer.

[0244] [Negative Electrode Active Material Layer]

[0245] The negative electrode active material layer is not particularly limited as long as it contains a negative electrode active material, but preferably contains a negative electrode active material and a solid electrolyte, and may further contain additives such as a conductive aid and a sintering aid.

[0246] The thickness of the negative electrode active material layer can be appropriately selected depending on the structure of the battery to be formed (thin film type, etc.), and is preferably 10 to 200 μm, more preferably 30 to 150 μm, and further preferably 50 to 100 μm.

[0247] Negative electrode active material

[0248] Examples of the negative electrode active material include lithium alloys, metal oxides, graphite, hard carbon, soft carbon, silicon, silicon alloys, silicon oxide SiO n (0<n≤2), silicon / carbon composite material, composite material containing silicon domains in pores of porous carbon, lithium titanate, and graphite coated with lithium titanate.

[0249] Among them, silicon / carbon composite materials and composite materials containing silicon domains in the pores of porous carbon have high specific capacity, can improve energy density and battery capacity, and are therefore preferred. More preferably, a composite material containing silicon domains in the pores of porous carbon has excellent slackness in volume expansion of silicon accompanying lithium absorption / release, and can well maintain the balance of macroscopic conductivity, microscopic conductivity and ion conductivity. Particularly preferred is a composite material in which the silicon domain is amorphous, the size of the silicon domain is less than 10nm, there are pores from porous carbon near the silicon domain, and the silicon domain is contained in the pores of porous carbon.

[0250] Preferred examples of the negative electrode active material include LiM3PO4 [M3 is one or more elements selected from Mn, Co, Ni, Fe, Al, Ti and V, or two elements of V and O], LiM5VO4 [M5 is one or more elements selected from Fe, Mn, Co, Ni, Al and Ti], Li2M6P2O7 [M6 is one or more elements selected from Fe, Mn, Co, Ni, Al, Ti and V, or two elements of V and O], LiVP2O7, Li x7 V y7 M7 z7 [2≤x7≤4, 1≤y7≤3, 0≤z7≤1, 1≤y7+z7≤3, M7 is one or more elements selected from Ti, Ge, Al, Ga and Zr], Li 1+x8 Al x8 M8 2-x8 (PO4)3[0≤x8≤0.8, M8 is one or more elements selected from Ti and Ge], (Li 3-a9x9+(5-b9)y9 M9 x9 )(V 1-y9 M10 y9 )O4[M9 is one or more elements selected from Mg, Al, Ga and Zn, M10 is one or more elements selected from Zn, Al, Ga, Si, Ge, P and Ti, 0≤x9≤1.0, 0≤y9≤0.6, a9 is the average valence of M9, b9 is the average valence of M10], LiNb2O7, Li4Ti5O 12 、Li4Ti5PO 12 , TiO2, LiSi, graphite.

[0251] The negative electrode active material is preferably in particulate form, and its 50% diameter in volume-based particle size distribution, aspect ratio, and 50% diameter in number-based particle size distribution of primary particles when the negative electrode active material forms secondary particles are preferably in the same range as those of the positive electrode active material.

[0252] The content of the negative electrode active material in the negative electrode active material layer is preferably 20 to 80% by volume, more preferably 30 to 70% by volume.

[0253] When the content of the negative electrode active material is within the above range, the negative electrode active material functions well, and there is a tendency that a battery with high energy density can be easily obtained.

[0254] Solid electrolyte

[0255] The solid electrolyte that can be used in the negative electrode active material layer is not particularly limited, and any conventionally known solid electrolyte can be used. However, the present electrolyte is preferably used from the viewpoint of further exerting the effects of the present invention.

[0256] The solid electrolyte used in the negative electrode active material layer may be one kind or two or more kinds.

[0257] ·additive

[0258] Preferred examples of the conductive additive include metal materials such as Ag, Au, Pd, Pt, Cu, and Sn, and carbon materials such as acetylene black, Ketjen black, carbon nanotubes, and carbon nanofibers.

[0259] As the sintering aid, the same compounds as the above-mentioned compound (b) are preferred.

[0260] The additives used in the negative electrode active material layer may be one kind or two or more kinds.

[0261] Negative electrode collector

[0262] As the negative electrode current collector, the same current collector as the positive electrode current collector can be used.

[0263] <Method for manufacturing all-solid-state battery>

[0264] All-solid batteries can be formed, for example, by a known powder molding method. For example, a positive electrode collector, a positive electrode active material layer powder, a solid electrolyte layer powder, a negative electrode active material layer powder, and a negative electrode collector are sequentially overlapped and powder molded at the same time, thereby simultaneously forming each layer of a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer, and connecting each of the positive electrode collector, the positive electrode active material layer, the solid electrolyte layer, the negative electrode active material layer, and the negative electrode collector.

[0265] When the powder is molded, it is preferred that the powder is fired at the same temperature as the firing temperature in the above step A while applying a pressure of the same degree as the pressure used when the material is press-molded in the above step A.

[0266] According to one embodiment of the present invention, even if the firing temperature during the manufacture of the all-solid-state battery is low, an all-solid-state battery with sufficient ion conductivity can be obtained, thereby being able to suppress the decomposition or deterioration of other materials such as positive electrode or negative electrode materials, thereby enabling the all-solid-state battery to be manufactured in an economical and equipment-saving manner.

[0267] Alternatively, the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer may be individually subjected to the above-mentioned powder molding, and when using the obtained layers to make an all-solid-state battery, each layer is preferably pressed and fired.

[0268] In addition, the all-solid-state battery can also be produced by the following method, for example.

[0269] By appropriately mixing a solvent, a resin, etc. in a material for forming a positive electrode active material layer, a material for forming a solid electrolyte layer, and a material for forming a negative electrode active material layer, a paste for forming each layer is prepared, and the paste is applied on a substrate and dried to produce a green sheet for a positive electrode active material layer, a green sheet for a solid electrolyte layer, and a green sheet for a negative electrode active material layer. Next, the substrate is peeled off from each green sheet, and the green sheet for the positive electrode active material layer, the green sheet for the solid electrolyte layer, and the green sheet for the negative electrode active material layer are sequentially stacked, and after being heat-pressed at a predetermined pressure, they are sealed in a container and pressurized by hot isostatic pressing, cold isostatic pressing, hydrostatic pressing, etc., to produce a stacked structure.

[0270] Then, if necessary, the stacked structure is subjected to a degreasing treatment at a predetermined temperature and then subjected to a sintering treatment to produce a stacked sintered body.

[0271] The firing temperature in this firing treatment is preferably the same temperature as the firing temperature in the above-mentioned step A.

[0272] Next, as necessary, a positive electrode current collector and a negative electrode current collector may be formed on both main surfaces of the stacked sintered body by sputtering, vacuum deposition, coating or dipping of a metal paste, etc., thereby producing an all-solid-state battery.

[0273] Example

[0274] Hereinafter, the present invention will be described in detail based on examples. However, the present invention is not limited to these examples.

[0275] [Synthesis Example 1] Synthesis of Li4B2O5

[0276] Lithium hydroxide monohydrate (LiOH·H2O) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., with a purity of 98.0% or more) and boric acid (H3BO3) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., with a purity of 99.5% or more) were weighed so that the atomic ratio of lithium to boron (Li:B) was 2.00:1.00. The weighed raw material powders were pulverized and mixed in an agate mortar for 15 minutes to obtain a mixture.

[0277] The obtained mixture was placed in an alumina container and heated to 500°C at a heating rate of 10°C / min in an atmosphere of air (flow rate: 100 mL / min) using a rotary sintering furnace (manufactured by Motoyama Co., Ltd.), and sintered at 500°C for 2 hours to obtain a primary sintered product.

[0278] The obtained primary fired product was crushed and mixed in an agate mortar for 15 minutes, and the obtained mixture was placed in an alumina container. Using a rotary sintering furnace (manufactured by Motoyama Co., Ltd.), the temperature was increased to 630°C at a heating rate of 10°C / min in an atmosphere of air (flow rate: 100 mL / min), and sintered at 630°C for 24 hours to obtain a secondary fired product (Li4B2O5).

[0279] The obtained secondary fired product was cooled to room temperature, taken out from the rotary firing furnace, and stored in a dehumidified nitrogen atmosphere.

[0280] [Synthesis Example 2] Synthesis of Li3BO3

[0281] Lithium hydroxide monohydrate (LiOH·H2O) (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., with a purity of 98.0% or more) and boric acid (H3BO3) (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., with a purity of 99.5% or more) are weighed so that the atomic ratio of lithium to boron (Li:B) becomes 3.00:1.00, and a secondary calcined product (Li3BO3) is obtained in the same manner as in Synthesis Example 1, except that the above preparation method is adopted.

[0282] [Synthesis Example 3] Synthesis of LiBiO2

[0283] Lithium hydroxide monohydrate (LiOH·H2O) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity of 98.0% or more) and bismuth oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity of 99.9%) were weighed so that the atomic ratio of lithium to bismuth (Li:Bi) was 1:1. The weighed raw material powders were pulverized and mixed in an agate mortar for 15 minutes to obtain a mixture.

[0284] The obtained mixture was placed in an alumina container and heated to 600°C at a heating rate of 10°C / min in an atmosphere of air (flow rate: 100 mL / min) using a rotary sintering furnace (manufactured by Motoyama Co., Ltd.), and sintered at 600°C for 4 hours to obtain a sintered product (LiBiO2).

[0285] The obtained fired product was cooled to room temperature, taken out from the rotary firing furnace, and stored in a dehumidified nitrogen atmosphere.

[0286] [Example 1]

[0287] An appropriate amount of toluene was added to tantalum pentoxide (Ta2O5) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity: 99.9%), and the mixture was pulverized for 2 hours using a zirconia ball mill (zirconia balls: 3 mm in diameter).

[0288] Next, lithium carbonate (Li2CO3) (manufactured by Sigma-Aldrich, with a purity of 99.0% or more), the crushed tantalum pentoxide (Ta2O5), the Li4B2O5 ​​obtained in the above-mentioned Synthesis Example 1, and diammonium hydrogen phosphate ((NH4)2HPO4) (manufactured by Sigma-Aldrich, with a purity of 98% or more) were weighed in the atomic ratio of lithium, tantalum, boron and phosphorus (Li:Ta:B:P) as shown in Table 1, and diammonium hydrogen phosphate was weighed in an amount that was 1.065 times the atomic weight of phosphorus in Table 1 in order to suppress the formation of by-products in the sintering process. An appropriate amount of toluene was added to each weighed raw material powder, and the mixture was pulverized and mixed for 2 hours using a zirconia ball mill (zirconia balls: 1 mm in diameter) to produce a solid electrolyte material.

[0289] The obtained solid electrolyte material was evaluated by powder X-ray diffraction described later and was found to be amorphous.

[0290] [Examples 2 to 4]

[0291] An amorphous solid electrolyte material was obtained in the same manner as in Example 1 except that the mixing ratio of the raw materials was changed so that the atomic ratios of lithium, tantalum, boron and phosphorus became as shown in Table 1.

[0292] The solid electrolyte material obtained in Example 3 was evaluated by powder X-ray diffraction described below. The half width of the diffraction peak at 28.59° with the maximum intensity confirmed in the range of 20°≤2θ≤40° was 1.03°, indicating that the material was amorphous.

[0293] [Example 5]

[0294] An appropriate amount of toluene was added to niobium pentoxide (Nb2O5) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity: 99.9%), and the mixture was pulverized for 2 hours using a zirconia ball mill (zirconia balls: 3 mm in diameter).

[0295] Next, on the basis of Example 1, the crushed niobium pentoxide (Nb2O5) was used instead of Li4B2O5, and the raw material powders were used in the manner shown in Table 1 with the atomic ratio of lithium, tantalum, niobium and phosphorus (Li:Ta:Nb:P). Except for this, the same preparation as Example 1 was carried out to obtain an amorphous solid electrolyte material.

[0296] [Examples 6 and 7]

[0297] On the basis of Example 5, Li4B2O5 ​​obtained in the above-mentioned synthesis example 1 was further used, and each raw material powder was used in the manner shown in Table 1 with the atomic number ratio of lithium, tantalum, niobium, boron and phosphorus. Except for this, the preparation was carried out in the same manner as Example 5 to obtain an amorphous solid electrolyte material.

[0298] [Examples 8 to 12]

[0299] On the basis of Example 1, Li3BO3 obtained in the above-mentioned Synthesis Example 2 was used instead of Li4B2O5, and the raw material powders were used in the manner shown in Table 1 with the atomic ratios of lithium, tantalum, boron and phosphorus. Except for this, the preparation was carried out in the same manner as Example 1 to obtain an amorphous solid electrolyte material.

[0300] [Example 13]

[0301] On the basis of Example 1, boric acid (H3BO3) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., with a purity of 99.5% or more) was used instead of Li4B2O5, and each raw material powder was used in the manner shown in Table 1 with the atomic ratio of lithium, tantalum, boron and phosphorus. Except for this, the same preparation as Example 1 was carried out to obtain an amorphous solid electrolyte material.

[0302] [Example 14]

[0303] On the basis of Example 1, lithium hydroxide monohydrate (LiOH·H2O) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., with a purity of 98.0% or more) was used instead of lithium carbonate, and each raw material powder was used in the manner shown in Table 1 with the atomic ratio of lithium, tantalum, boron and phosphorus. Except for this, the production was carried out in the same manner as Example 1 to obtain an amorphous solid electrolyte material.

[0304] [Example 15]

[0305] On the basis of Example 1, lithium acetate (CH3COOLi) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., with a purity of 98.0% or more) was used instead of lithium carbonate, and each raw material powder was used in the manner shown in Table 1 with the atomic ratio of lithium, tantalum, boron and phosphorus. Except for this, the preparation was carried out in the same manner as Example 1 to obtain an amorphous solid electrolyte material.

[0306] [Example 16]

[0307] On the basis of Example 1, silicon oxide (SiO2) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., with a purity of 99.9%) was used instead of Li4B2O5, and the raw material powders were used in the manner shown in Table 1 with the atomic ratios of lithium, tantalum, phosphorus and silicon. Except for this, the production was carried out in the same manner as Example 1 to obtain an amorphous solid electrolyte material.

[0308] [Examples 17 to 19]

[0309] On the basis of Example 1, silicon oxide (SiO2) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., with a purity of 99.9%) was further used, and each raw material powder was used in the manner shown in Table 1 with the atomic ratio of lithium, tantalum, boron, phosphorus and silicon. Except for this, the production was carried out in the same manner as Example 1 to obtain an amorphous solid electrolyte material.

[0310] [Examples 20 to 24]

[0311] On the basis of Example 8, silicon oxide (SiO2) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., with a purity of 99.9%) was further used, and each raw material powder was used in the manner shown in Table 1 with the atomic number ratio of lithium, tantalum, boron, phosphorus and silicon. Except for this, the production was carried out in the same manner as Example 8 to obtain an amorphous solid electrolyte material.

[0312] [Example 25]

[0313] On the basis of Example 1, LiBiO2 obtained in Synthesis Example 3 was used instead of Li4B2O5, and the raw material powders were used in the manner shown in Table 1 with the atomic ratios of lithium, tantalum, bismuth and phosphorus. Except for this, the preparation was carried out in the same manner as Example 1 to obtain an amorphous solid electrolyte material.

[0314] [Example 26]

[0315] On the basis of Example 25, silicon oxide (SiO2) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., with a purity of 99.9%) was further used, and the raw material powders were used in the manner shown in Table 1 with the atomic ratio of lithium, tantalum, bismuth, phosphorus and silicon (Li:Ta:Bi:P:Si). Except for this, the production was carried out in the same manner as Example 25 to obtain an amorphous solid electrolyte material.

[0316] [Comparative Example 1]

[0317] Lithium carbonate (Li2CO3) (manufactured by Sigma-Aldrich, purity of 99.0% or more), tantalum pentoxide (Ta2O5) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity of 99.9%), and diammonium hydrogen phosphate ((NH4)2HPO4) (manufactured by Sigma-Aldrich, purity of 98% or more) were weighed in such a manner that the atomic ratio of lithium, tantalum, and phosphorus (Li:Ta:P) was as shown in Table 1. Furthermore, in consideration of lithium atoms flowing out of the system during the calcination process, lithium carbonate was weighed in an amount that was 1.1 times the atomic weight of lithium in Table 1. Furthermore, in order to suppress the generation of by-products during the calcination process, diammonium hydrogen phosphate was weighed in an amount that was 1.065 times the atomic weight of phosphorus in Table 1. An appropriate amount of toluene was added to each weighed raw material powder, and the mixture was pulverized and mixed for 2 hours using a zirconia ball mill (zirconia balls: diameter 1 mm).

[0318] The obtained mixture was placed in an alumina container and heated to 1000°C at a heating rate of 10°C / min in an atmosphere of air (flow rate: 100 mL / min) using a rotary sintering furnace (manufactured by Motoyama Co., Ltd.), and sintered at 1000°C for 4 hours to obtain a primary sintered product.

[0319] The primary fired product was crushed and mixed in an agate mortar for 15 minutes, and the mixture was placed in an alumina container. The mixture was heated to 1000°C at a rate of 10°C / min in a rotary sintering furnace (manufactured by Motoyama Co., Ltd.) in an atmosphere of air (flow rate: 100 mL / min), and fired at 1000°C for 1 hour to obtain a secondary fired product.

[0320] An appropriate amount of toluene was added to the obtained fired product, and the mixture was pulverized and mixed for 2 hours using a zirconia ball mill (zirconia balls: 1 mm in diameter), thereby obtaining an amorphous solid electrolyte material.

[0321] [Comparative Example 2]

[0322] An amorphous solid electrolyte material was obtained in the same manner as in Comparative Example 1 except that the mixing ratio of the raw materials was changed so that the atomic ratio of lithium, tantalum and phosphorus became the amount described in Table 1.

[0323] [Example 27]

[0324] Lithium carbonate (Li2CO3) (manufactured by Sigma-Aldrich, with a purity of 99.0% or more), tantalum pentoxide (Ta2O5) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., with a purity of 99.9%), Li4B2O5 ​​(Synthesis Example 1), and diammonium hydrogen phosphate ((NH4)2HPO4) (manufactured by Sigma-Aldrich, with a purity of 98% or more) were weighed in the atomic ratio of lithium, tantalum, boron and phosphorus (Li:Ta:B:P) as shown in Table 2. In order to suppress the formation of by-products in the sintering process, diammonium hydrogen phosphate was weighed in an amount that was 1.065 times the atomic weight of phosphorus in Table 2. An appropriate amount of toluene was added to each weighed raw material powder, and the mixture was pulverized and mixed for 2 hours using a zirconia ball mill (zirconia balls: 1 mm in diameter) to obtain a solid electrolyte material.

[0325] The obtained solid electrolyte material was evaluated by powder X-ray diffraction described later. The half width of the diffraction peak at 22.89° with the maximum intensity confirmed in the range of 20°≤2θ≤40° was 0.29°, indicating that the solid electrolyte material was amorphous.

[0326] [Comparative Example 3]

[0327] Lithium carbonate (Li2CO3) (manufactured by Sigma-Aldrich, purity of 99.0% or more), tantalum pentoxide (Ta2O5) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity of 99.9%), Li4B2O5 ​​(Synthesis Example 1), and diammonium hydrogen phosphate ((NH4)2HPO4) (manufactured by Sigma-Aldrich, purity of 98% or more) were weighed in a manner such that the atomic ratio of lithium, tantalum, boron and phosphorus (Li:Ta:B:P) was as shown in Table 2. Furthermore, in consideration of lithium atoms flowing out of the system during the calcination process, lithium carbonate was weighed in an amount that was 1.1 times the atomic weight of lithium in Table 2. Furthermore, in order to suppress the generation of by-products during the calcination process, diammonium hydrogen phosphate was weighed in an amount that was 1.065 times the atomic weight of phosphorus in Table 2. An appropriate amount of toluene was added to each weighed raw material powder, and the mixture was pulverized and mixed for 2 hours using a zirconia ball mill (zirconia balls: diameter 1 mm).

[0328] The obtained mixture was placed in an alumina container and heated to 1000°C at a heating rate of 10°C / min in an atmosphere of air (flow rate: 100 mL / min) using a rotary sintering furnace (manufactured by Motoyama Co., Ltd.), and sintered at 1000°C for 4 hours to obtain a solid electrolyte material.

[0329] The obtained solid electrolyte material was evaluated by powder X-ray diffraction described later, and the half-value width of the diffraction peak at 25.39° with the maximum intensity confirmed in the range of 20°≤2θ≤40° was 0.11°, indicating that the solid electrolyte material was crystalline.

[0330] <Powder X-ray Diffraction (XRD)>

[0331] The obtained solid electrolyte material was subjected to X-ray diffraction measurement (Cu-Kα ray (output: 45 kV, 40 mA), diffraction angle 2θ = 10 to 50°, step width: 0.013°, incident side Sollerslit: 0.04 rad, incident side Anti-scatter slit: 2°, light receiving side Sollerslit: 0.04 rad, light receiving side Anti-scatter slit: 5 mm) using a powder X-ray diffraction measuring apparatus Panalytical MPD (manufactured by Spectris Corporation) to obtain an X-ray diffraction (XRD) pattern. The obtained XRD pattern was subjected to Rietveld analysis using the known analysis software RIETAN-FP (available from the homepage of the creator Fujio Izumi, "RIETAN-FP·VENUS System Distribution File" (http: / / fujioizumi.verse.jp / download / download.html)), thereby confirming the crystal structure.

[0332] The half-value width is calculated by fitting using a Pseudo Voigt function by a nonlinear least square method. The Pseudo Voigt function used is a function of linearly combining a Gaussian function and a Lorentzian function having the same half-value width by weight, and is specifically represented by the following formula (1).

[0333]

[0334] [c is the intensity of the background, A is the peak area, m is the weight of the Gaussian function and the Lorentzian function and 0≤m≤1, ω is the half-value width of the diffraction peak, x0 is the diffraction angle of the diffraction peak]

[0335] The XRD patterns of the solid electrolyte materials obtained in Example 3, Example 27 and Comparative Example 3 are shown in Figure 1 , Figure 2 and Figure 3 .

[0336] In addition, the results of fitting the diffraction peaks with the maximum intensity that can be confirmed in the range of 20°≤2θ≤40° in the XRD patterns of the solid electrolyte materials obtained in Example 3, Example 27 and Comparative Example 3 using the above method are shown in FIG. Figure 4 , Figure 5 and Figure 6 .

[0337] In Tables 1 and 2, Figure 4 , Figure 5 The case where the half-value width of the diffraction peak with the maximum intensity that can be confirmed in the range of 20°≤2θ≤40° is greater than 0.15° is defined as "amorphous". Figure 6 In this way, the case where the half-value width of the diffraction peak with the maximum intensity confirmed in the range of 20°≤2θ≤40° is 0.15° or less is regarded as "crystalline".

[0338] <Production of pellets>

[0339] A tablet molding machine was used to apply a pressure of 40 MPa to the obtained solid electrolyte material using a hydraulic press, thereby forming a disc-shaped molded body with a diameter of 10 mm and a thickness of 1 mm. Then, a pressure of 300 MPa was applied to the disc-shaped molded body by CIP (cold isostatic pressing) to produce particles.

[0340] <Production of sintered body>

[0341] The obtained particles are placed in an alumina container and heated using a rotary sintering furnace (manufactured by Motoyama Co., Ltd.) in an atmosphere of air (flow rate: 100 mL / min) at a heating rate of 10°C / min to the temperature recorded in the total conductivity column of Table 1 (650°C, 700°C, 750°C or 850°C), and sintered at this temperature for 96 hours to obtain a sintered body.

[0342] The obtained sintered product was cooled to room temperature, taken out from the rotary sintering furnace, and stored in a dehumidified nitrogen atmosphere.

[0343] <Total conductivity>

[0344] A gold layer was formed on both surfaces of the obtained sintered body using a sputtering machine, thereby obtaining measurement particles for evaluating ion conductivity.

[0345] The obtained measurement particles were kept in a constant temperature bath at 25°C for 2 hours before measurement. Next, at 25°C, an impedance analyzer (manufactured by Solartron Analytical, model: 1260A) was used to perform AC impedance measurement in the frequency range of 1 Hz to 10 MHz under the condition of an amplitude of 25 mV. Using the equivalent circuit analysis software ZView attached to the device, the obtained impedance spectrum was fitted with an equivalent circuit, and the conductivity of each lithium ion in the grain and at the grain boundary was calculated, and they were added together to calculate the total conductivity. The results are shown in Table 1 or 2. In addition, the total conductivity of the sintered body obtained by sintering the solid electrolyte material obtained in Comparative Example 1 at 650°C was too low, and no measured value was obtained.

[0346] Table 1

[0347]

[0348] As can be seen from Table 1, an amorphous solid electrolyte material containing lithium, tantalum, phosphorus and oxygen as constituent elements and at least one element selected from boron, niobium and bismuth as a constituent element can obtain a sintered body with sufficient total conductivity even when sintered at a low temperature below 900°C.

[0349]

[0350] As can be seen from Table 2, although the amorphous solid electrolyte material contains lithium, tantalum, phosphorus and oxygen as constituent elements and contains boron as a constituent element, it is possible to obtain a sintered body having sufficient total conductivity even when sintered at a low temperature of 900°C or below.

Claims

1. A solid electrolyte material, which is amorphous and contains lithium, tantalum, phosphorus and oxygen as constituent elements, and contains at least one element selected from boron, niobium, silicon and bismuth as a constituent element, The content of tantalum element is 10.6~16.6 atomic% The phosphorus content is 5.3-8.8 atomic %. The content of lithium element is 5.0 to 20.0 atomic %. When the solid electrolyte material contains boron, the content of boron is 0.1 to 5.0 atomic %. When the solid electrolyte material contains niobium, the content of niobium is 0.1 to 5.0 atomic %. When the solid electrolyte material contains silicon, the content of silicon is 0.1 to 5.0 atomic %. When the solid electrolyte material contains bismuth element, the content of bismuth element is 0.1 to 5.0 atomic %. 2 . The solid electrolyte material according to claim 1 , comprising one or more elements selected from the group consisting of Zr, Ga, Sn, Hf, W, Mo, Al and Ge as constituent elements.

3. A solid electrolyte obtained by using the solid electrolyte material according to claim 1 or 2.

4. A solid electrolyte which is a sintered body of the solid electrolyte material according to claim 1 or 2.

5. A method for producing a solid electrolyte, comprising the step of calcining the solid electrolyte material according to claim 1 or 2 at 500 to 900°C, wherein the solid electrolyte is the solid electrolyte according to claim 3 or 4.

6. An all-solid-state battery comprising a positive electrode, a negative electrode and a solid electrolyte layer, The positive electrode has a positive electrode active material, The negative electrode has a negative electrode active material, The solid electrolyte layer is located between the positive electrode and the negative electrode, The solid electrolyte layer includes the solid electrolyte according to claim 3 or 4.

7. The all-solid-state battery according to claim 6, wherein the positive electrode active material comprises a material selected from the group consisting of LiM3PO4, LiM5VO4, Li2M6P2O7, LiVP2O7, Li x7 V y7 M7 z7 , Li 1+x8 Al x8 M8 2-x8 (PO4)3、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiCoO2, LiNiO2, LiMn2O4, Li2CoP2O7, Li3V2(PO4)3, Li3Fe2(PO4)3, LiNi 0.5 Mn 1.5 O4 and Li4Ti5O 12 One or more compounds of M3 is one or more elements selected from Mn, Co, Ni, Fe, Al, Ti and V, or two elements V and O, M5 is one or more elements selected from Fe, Mn, Co, Ni, Al and Ti, M6 is one or more elements selected from Fe, Mn, Co, Ni, Al, Ti and V, or two elements V and O, 2≤x7≤4, 1≤y7≤3, 0≤z7≤1, 1≤y7+z7≤3, M7 is one or more elements selected from Ti, Ge, Al, Ga and Zr, 0≤x8≤0.8, M8 is one or more elements selected from Ti and Ge.

8. The all-solid-state battery according to claim 6 or 7, wherein the negative electrode active material comprises a material selected from the group consisting of LiM3PO4, LiM5VO4, Li2M6P2O7, LiVP2O7, Li x7 V y7 M7 z7 , Li 1+x8 Al x8 M8 2-x8 (PO4)3、(Li 3-a9x9+(5-b9)y9 M9 x9 )(V 1- y9 M10 y9 )O4, LiNb2O7, Li4Ti5O 12 、Li4Ti5PO 12 , TiO2, LiSi and graphite, M3 is one or more elements selected from Mn, Co, Ni, Fe, Al, Ti and V, or two elements V and O, M5 is one or more elements selected from Fe, Mn, Co, Ni, Al and Ti, M6 is one or more elements selected from Fe, Mn, Co, Ni, Al, Ti and V, or two elements V and O, 2≤x7≤4, 1≤y7≤3, 0≤z7≤1, 1≤y7+z7≤3, M7 is one or more elements selected from Ti, Ge, Al, Ga and Zr, 0≤x8≤0.8, M8 is one or more elements selected from Ti and Ge, M9 is one or more elements selected from Mg, Al, Ga and Zn, M10 is one or more elements selected from Zn, Al, Ga, Si, Ge, P and Ti, 0≤x9≤1.0, 0≤y9≤0.6, a9 is the average price of M9, and b9 is the average price of M10.

9. The all-solid-state battery according to claim 6, The positive electrode and the negative electrode contain the solid electrolyte according to claim 3 or 4.

Citation Information

Patent Citations

  • Glass electrolyte

    JP2015063447A

  • Glass ceramic that conducts lithium ions, and use of said glass ceramic

    US20140057162A1

  • Solid electrolyte and all solid state battery

    US20200106131A1